Business Model Canvas (BMC) dalam Pengembangan Bisnis Fashion Muslim - Setya Indah Isnawati; Jaya Ramadaey Bangsa; Noor Laila Ramadhani (Jurnal Dinamika Ekonomi & Bisnis, 2023)
The fashion industry in Indonesia needs business growth methods to withstand the Covid-19 epidemic and the growing cost of essential supplies. Kedjora Grosir is a micro, small, and medium-sized enterprise (MSME) in the Magelang Regency that deals in Muslim clothing and accessories, and it needs a plan to survive and grow in the face of the ongoing COVID-19 epidemic. The method employed was the Business Model Canvas (BMC). Qualitative descriptive methods were used, with both primary and secondary sources, to complete the study. The objective of the study is to use the Company Model Canvas (BMC) and the SWOT analysis to choose a winning business plan (Strength, Weakness, Opportunity and Threat). Incorporating e-commerce companies as business partners, developing websites for product marketing, and working with the young mothers’ community were components of the research and the findings of the SWOT analysis constituted an improvement plan. The value proposition also includes advising shoppers on how best to pair various clothing items. The owner of Kedjora Grosir, a Muslim clothing retailer, can use the study findings to shape the company's future